METASOMATIC FORMATION OF POIKILITIC CRYSTALS: EXPERIMENTAL MODELING - Glikin A.E.; Sinai M.Yu. (My University, 2004)
In publications, data on quadruple systems are scarce. The preliminary information on the polymineral replacement can be inferred from metasomatic relationships between salt pairs of the system, which are shown by isotherm configurations on planes formed by coordinate axes. Our data on processes in triple subsystems of the quadruple system being considered show that the replacement of crystal CoSO4 · 7H2O in solution FeSO4 · 7H2O produces a volume-deficient (isomorphic) monocrystalline pseudomorph, whereas the replacement of CoSO4 · 7H2O crystal in solution Fe(NH42(SO4)2 · 6H2O produces a polycrystalline pseudomorph. In this case, the formation of poikilitic aggregate (combined mono- and polycrystalline pseudomorph) corresponds to products of reactions in triple subsystems.